2021 Analysis of Elderly people living in Briddha Ashram - Subedi, Bed Kumari (PRAGYAN A Peer Reviewed Multidisciplinary Journal, 2021)
Ageing is a natural phenomenon and an inevitable process. Population ageing is pervasive since it is creating humanitarian, social and economic problems in many countries of the world including Nepal. Nepalese society is in a phase of modernization. There is modification in the cultural norms and traditional family support systems for elderly in Nepal which have placed substantial strain in caring elderly people. In Nepal, there were 1.5 million in 2001 and 2.1 million in 2011, elderly inhabitants, which constitute 6.5 percent and 8.1 % of the total population in the country. During the years 1991-2001, the annual elderly population growth rate was 3.39 percent, higher than the annual population growth rate of 2.3 percent. Growing numbers of elderly people are suffering problems in different aspect, but there are limited studies in relation to general morbidities as well as specific in this group of people. The government of Nepal has formulated a National policy, act and regulations on ageing and the problems of elderly; however, this has not been operationalised because of limited resources. In this background of problems that elderly people are facing and government slow initiatives, this paper is illustrated with the objective to explore the different dimensions of ageing and health and health related services for aging people in Nepal using different information for the purpose of further concrete steps in the benefits for elders.